PERFORMANCE OPTIMIZATION OF SOLAR PV MODULE USING PHASE CHANGE MATERIAL - A. A. IMAM; I. MAINA; O. W. OLASOJI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Controlling the surface temperature of a typical solar photovoltaic module is key in achieving higher efficiency. Apt cooling can improve the electrical performance and bring down the rate of the PV module’s degradation. An integrated passive cooling technique is presented in this paper. A 0.5cm thick phase change material (paraffin wax) was incorporated in a commercially available photovoltaic PV module. Concurrently, the fabricated (cooled) and the reference (without cooling) PV modules were subjected to the same operational conditions for 5 consecutive days. The electrical parameters of the duo were recorded at a regular interval of time. The average power generated by each are; 8.12W and 9.58W for the reference and fabricated PV modules respectively. This yielded an average power gain of 18% for fabricated module over reference one. Similarly, the average surface temperature of the reference module is 50°C and that of the fabricated module was 46.5°C against 38.4°C of atmospheric temperature. With paraffin wax being inexpensive and available, a more efficient solar photovoltaic module can be achieved through this technique.